Algebra 1 help.. Please?

1 year ago
(6x^3 − 8x − 5) + (3x^3 + 6x + 2).

9x^3-2x -3
TAG:
Best Answer
1. 6th degree binomial (D)
2. x^4y^2 + 4x^2y + 8x (B)
3. 6x^3 - 8x - 5 + 3x^3 + 6x + 2 = 9x^3 - 2x - 3 (A)
4. product of powers (C)
5. (2x^2 y^6 z^5)(5x^4 y^5 z^3) = 10x^6 y^11 z^8 (D)
6. (5a^7b)^2 = (5a^7b)(5a^7b) = 25a^14b^2 (D)
7. (2x^7y)^2 (y^5)^3 = 4x^14y^2 y^15 = 4x^14 y^17 (D)
8. (a^9 * b^10) / (a^2 * b^7) = a^7b^3 (D)
9. (a^3/b^7)^2 = (a^6)/(b^14) (C)
10. (4*b)/a^-10 = 4a^10b (B)
11. (-11x^3y^12z^3)^0 = 1 (D)
12. -3x^2 (5x - 4x^2 - 6) = 12x^4 - 15x^3 + 18x^2 (B)
13. (-2x + 10y)(4x - 6y) = -8x^2 + 52xy - 60y^2 (B)
14. (2x - 6)(3x^2 - 3x - 6) = 6x^3 - 24x^2 + 6x + 36 (A)
15. (6x + 2)^2 = (6x + 2)(6x + 2) = 36x^2 + 24x + 4 (D)
16. (7x - 6)^2 = (7x - 6)(7x - 6) = 49x^2 - 84x + 36 (D)
17. (6x - 2)(6x+ 2) = 36x^2 - 4 (D)
18. ??
19. ((-5)(x^3) + 20(x^2) - 25(x)) / -5x = x^2 - 4x + 5 (C)
20. (-5x^2 - x^3 - 3) - (9x^3 + 3x - 6x^2) = -10x^3 + x^2 - 3x - 3
Other Answers